Between minimal and greater than minimal risk: how research participants and oncologists assess data-sharing and the risk of re-identification in genomic research - Schleidgen, Sebastian; Husedzinovic, Alma; Ose, Dominik; Schickhardt, Christoph; Kalle, Christof von; Winkler, Eva C. (Philosophy & technology, 2019)
Data-sharing among genomic researchers is promoted for its potential to accelerate our understanding of the molecular basis of cancer. However, with genomic data sharing the risks of re-identifying study participants, revealing personal genomic information and data misuse might increase. This study aims at exploring perceptions of patients and physicians in Oncology regarding their assessment of the informational risks resulting from participating in whole genomic research studies in order to improve the informed consent process. For this purpose, we conducted a qualitative focus group study at the National Center for Tumor Diseases (NCT). Patients and oncologists assessed the informational risks either as minimal or as greater than minimal, depending on the context factors of occupational status, age, and patients’ prognosis. Interestingly, even patients who assumed a greater risk did not refrain from participating in genomic research, provided that certain informational and institutional safeguards are implemented. Moreover, they expected comprehensive disclosure of the risks resulting from genomic data sharing. These results suggest (1) comprehensive disclosure of the risks of genomic research to potential study participants in genomic research to facilitate risk assessment and sound decision making, (2) establishing independent governance entities in order to minimize the informational risks of genomic research, and (3) implementing data sharing policies which offer guidance for physicians and researchers involved in genomic research.
Published online: 5 June 2017
Gesehen am 23.04.2021